Evaluación y determinación de la capacidad secuestrante de los metales pesados cromo (CR) y cadmio (CD) por taxas de mohos aisladas de los alrededores de los ríos Cutuchi y Machángara - Hidalgo Ramírez, Carina Elizabeth (2013)
Heavy metals are now a major source of environmental pollution, caused mostly by man's industrial activities, fortunately some living organisms because of their adaptability to the environment, can provide remediation alternatives for these pollutants, for this reason in this work we evaluated the sequestering capacity of Chromium (Cr) and Cadmium (Cd) by mold’s taxas isolated from sediments on the banks of wetlands in the rivers Cutuchi and Machángara. There were isolated a total of 63 mold’s taxas, of which, eight were selected considering its growth in agar plate modified with 45 ppm Cr and Cd. The selected taxas corresponded to the genus Mucor sp., Rhizopus sp. and Trichoderma sp., which were subsequently evaluated at 100 ppm Cr and Cd respectively in a modified liquid medium.